COVID-19 musculoskeletal involvement in children - Chiara Giraudo; Giulia Fichera; Lucia Pilati; Anna Laura Cortinovis; Celeste Cavallin; Sofia Bertin; Monica Zuliani; Diego Cecchin (Frontiers Media S.A., 2023)
Since the early phases of the COVID-19 pandemic, it has become clear that children are affected by mild respiratory symptoms rather than the critical pneumonia typical in adults. Nevertheless, it took longer to understand that pediatric patients with SARS-COV2 may develop a severe multisystem inflammatory response (a.k.a. multisystem inflammatory syndrome in children (MIS-C)), which can include musculoskeletal symptoms, and/or arthritis and myositis independently from MIS-C. Diagnostic imaging significantly contributed to the assessment of pulmonary disease due to COVID-19 but it has been rarely applied to evaluate musculoskeletal involvement in children with or without previous rheumatic diseases. Despite the paucity of radiological literature, muscle edema at magnetic resonance and synovitis at ultrasound have been described. Further use of diagnostic imaging for children with articular and muscular symptoms due to COVID-19 is strongly encouraged.